2014
DOI: 10.1186/2197-5620-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Ingrowth, survival and height growth of small trees in uneven-aged Picea abies stands in southern Finland

Abstract: The purpose of the study was to analyse height growth, mortality, and ingrowth of individual small-sized trees in uneven-aged spruce-dominated stands. It was based on experimental data from 16 stands for a 15-year observation period including four measurements with a 5-year interval. In the data of this study, the heights of small-sized trees varied from 0.1 to about 9 m. Results showed that the growth of small trees was rather slow, particularly in the smallest size classes. With average growth rates it would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 32 publications
2
24
2
Order By: Relevance
“…Based on simulations with the model constructed in this study, it would take 11-12 years for a 10 cm-tall spruce seedling to reach a height of 1.3 m. If an assumption is made that for a spruce seedling it takes three to five years to reach 10 cm (Hökkä et al 2011), breast height can be reached in 20 years or less in the gaps of this study site. That would be significantly quicker when compared to the average of 60 years in an uneven-aged stand in southern Finland mineral soil sites (Eerikäinen et al 2014), or 24-47 years as reported by Lundqvist (1989) from mineral soil sites in Sweden. One possible reason may be that after uneven-aged cutting in the more southerly located mineral soils sites, the retained stand remains rather stocked (Eerikäinen et al 2014) and conditions more shady than after cutting canopy gaps in naturally more open (e.g., Heikurainen 1971;Norokorpi et al 1997) spruce mire stands in northern Finland.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Based on simulations with the model constructed in this study, it would take 11-12 years for a 10 cm-tall spruce seedling to reach a height of 1.3 m. If an assumption is made that for a spruce seedling it takes three to five years to reach 10 cm (Hökkä et al 2011), breast height can be reached in 20 years or less in the gaps of this study site. That would be significantly quicker when compared to the average of 60 years in an uneven-aged stand in southern Finland mineral soil sites (Eerikäinen et al 2014), or 24-47 years as reported by Lundqvist (1989) from mineral soil sites in Sweden. One possible reason may be that after uneven-aged cutting in the more southerly located mineral soils sites, the retained stand remains rather stocked (Eerikäinen et al 2014) and conditions more shady than after cutting canopy gaps in naturally more open (e.g., Heikurainen 1971;Norokorpi et al 1997) spruce mire stands in northern Finland.…”
Section: Discussionmentioning
confidence: 77%
“…In this study the average growth was two to three times better than in uneven-aged harvest stands observed in southern Finland by Eerikäinen et al (2014) or in Sweden (Lundqvist 1989). Based on simulations with the model constructed in this study, it would take 11-12 years for a 10 cm-tall spruce seedling to reach a height of 1.3 m. If an assumption is made that for a spruce seedling it takes three to five years to reach 10 cm (Hökkä et al 2011), breast height can be reached in 20 years or less in the gaps of this study site.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations